The accidental birth of “official development assistance” - Scott, Simon (OECD Development Co-operation Working Papers, 2015)
Official development assistance (ODA) has been the standard measure of foreign aid for 45 years, but its creation was largely accidental, and followed no plan. Its origins lie with efforts by the OECD’s Development Assistance Committee (DAC) in the early 60s to soften and harmonise the terms of aid to developing countries. The DAC agreed a first Recommendation on aid terms in 1965, but its targets were complex and its quantities not adequately defined. An underlying difficulty was identifying which loans were soft enough to count as aid and thus be subject to the disciplines. Among metrics for valuing the concession embodied in loans, the “grant element” methodology proved the most fruitful, and it was used to refine the targets in a 1969 Supplement to the Recommendation. That Supplement introduced the idea of “official development assistance”, but without defining it. It was not until the 1972 revision of the Terms Recommendation that ODA was fully defined. This included setting a minimum grant element for an ODA loan and a single target for the overall “softness” of aid programmes. Special terms targets were agreed for a new category of Least Developed Countries. Though not perfect, the 1972 decisions created an integrated and fully specified system for monitoring aid volume and softening aid terms. The process that produced this result turned on interactions between the OECD and the UN system that helped generate the required innovations in concepts and techniques.